The role of international media in shaping public opinion trends during armed conflicts - Валид Набиль Саяд; Фади Алаззех С. А. (Знак: проблемное поле медиаобразования, 2024)
The research deals with the characteristics of the formation of public opinion during armed conflicts. It aims to study and analyze the role played by the media in the formation of public opinion during conflicts. The purpose of this research is to provide a deeper understanding of the complex relationship between the media and public opinion in the context of issues of armed conflict. The research problem is the challenges facing the formation of an objective and conscious public opinion during armed conflicts, given the growing influence of disinformation, propaganda, and censorship on the media. The research seeks to understand the main characteristics of the formation of public opinion during armed conflicts, the media strategies used to control public opinion during armed conflicts, and how the media affects public perceptions and attitudes towards the parties to the conflict.